Revision of the Afrotropical flea beetle subgenus Blepharidina s. str. Bechyné (Coleoptera, Chrysomelidae) - D’alessandro, Paola; Iannella, Mattia; Biondi, Maurizio (Zootaxa, 2019)
A taxonomic revision of the species attributed to the flea beetle subgenus Blepharidina s. str. Bechyné, 1968 from sub-Saharan Africa is provided. The subgenus comprises 20 species, including the following six new species here described: B. aliquantula sp. nov. from Somalia, B. himba sp. nov. from Namibia, B. kasigauensis sp. nov., B. kenyana sp. nov., B. regalini sp. nov. from Kenya, and B. matabelelandensis sp. nov. from Zimbabwe. A key to all the species is given, with photos of their habitus, aedeagus, spermatheca, and main external diagnostic characters. Taxonomic notes, with considerations on similarities and affinities, and ecological data on the habitat preference for each species, are also reported.